Catechol-based layer-by-layer assembly of composite coatings: a versatile platform to hierarchical nano-materials1. Issue 31 (21st August 2015) - Wang, C. X.; Braendle, A.; Menyo, M. S.; Pester, C. W.; Perl, E. E.; Arias, I.; Hawker, C. J.; Klinger, D.
<x xml:space="preserve">Abstract</x> Inspired by the marine mussel's ability to adhere to surfaces underwater, an aqueous catechol-based dip coating platform was developed to enable facile fabrication of robust composite coatings and Bragg stacks.